2018
DOI: 10.3126/jonmc.v7i2.22304
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome of permanent pacemaker implantation

Abstract: Background: Permanent pacemaker implantation (PPI) is considered the most effective and safe procedure for treatment of symptomatic bradyarrythmia. In this study we evaluated incidence of intraoperative and early postoperative (three month) outcome of PPI in our center. Method: This is a cross sectional study carried out over a period twenty months between Jan 2017 and August 2018. All patients undergoing PPI at Nobel Medical College were enrolled in the study. Details of demographic data, medical histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 7 publications
6
8
0
Order By: Relevance
“…The most common indication for PPI was CHB followed by SSS. Similar findings were noted in study done by Khanal J et al 9 and Jha S et al 11 whereas study done by Monib A et al 10 showed much higher incidence of CHB (87%) than our study. Annual report of SGNHC showed 65-78% incidence of CHB but much lesser incidence of SSS (6-9%) compared to our study 13 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The most common indication for PPI was CHB followed by SSS. Similar findings were noted in study done by Khanal J et al 9 and Jha S et al 11 whereas study done by Monib A et al 10 showed much higher incidence of CHB (87%) than our study. Annual report of SGNHC showed 65-78% incidence of CHB but much lesser incidence of SSS (6-9%) compared to our study 13 .…”
Section: Discussionsupporting
confidence: 92%
“…Only 13 women (11.6%) received dual chamber pacemaker compared with 36 men (21.8%) (P = 0.029). Other studies published in Nepal also show similar incidence of single chamber pacemakers over dual chamber ones 9,10,13 . The finding of the study done in Australia is different with our study, which revealed that 74% of the patients received a dual chamber pacemaker 14 .…”
Section: Age Groupmentioning
confidence: 51%
See 2 more Smart Citations
“…2 There are few studies and reports have been published regarding clinical profile, short term outcome, experiences in pacemaker implantation in different center in our part of the world. [3][4][5][6][7] This study intended focusing on permanent pacemaker implantation (PPI) of 19 years data at the referral tertiary cardiac center which will highlight and reflect a clear picture of the trends and profile of PPI implantation in Nepal.…”
Section: Introductionmentioning
confidence: 99%